Car Selling Without Price Negotiations: Wishful Thinking or the New Normal? - Mario Farsky; Julian Feldhäuser; Ferdinand Harries; Andrej Levin; Dominik Papies (Marketing Review St.Gallen, 2024)
Leading global car manufacturers are targeting a shift to direct sales with fixed, non-negotiable prices, yet consumer responses to such a paradigm shift remain largely unexplored. Our study of 500 consumers reveals that in the current market environment, two-thirds would engage in price negotiations, yet the same proportion would pay a mark-up to avoid this common practice. The findings suggest that a carefully planned transition to fixed prices, slightly below current offer prices, could be accepted by consumers, potentially ushering in a new era in automotive retail.
Keywords: 650